Kinetics and Mechanism of Pd(II) Catalyzed Oxidation of Valine and Leucine by Acidic Solution of Chloramine-T - SINGH, R.A.; SRIVASTAVA, V.K.; VERMA, JYOTI; KUMAR, MITHILESH (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of amino acid (valine and leucine) by acidic solution of chloramine-T have been studied in the presence of PdCl2 as catalyst. The order of reaction in chloramine-T and substrate is unity but the acidic medium (H+) shows inverse first order. The reaction also shows first order with respect to Pd(II) under experimental conditions. ([H+] >> [PdCl2]). A mechanism involing [Pd(II) - AA] (where AA = amino acid) intermediate complexes is proposed.